2017
DOI: 10.1017/s0007485317000347
|View full text |Cite
|
Sign up to set email alerts
|

Limited impacts of truck-based ultra-low-volume applications of mosquito adulticides on mortality in honey bees (Apis mellifera)

Abstract: Adulticides applied against mosquitoes can reduce vector populations during times of high arbovirus transmission. However, impacts of these insecticides on pollinators and other non-target organisms are of concern to mosquito control professionals, beekeepers and others. We evaluated mortality of Culex quinquefasciatus and Apis mellifera when caged insects were exposed to low and high label rates of four common adulticides (Aqua-Pursuit™ [permethrin], Duet® [prallethrin + sumithrin], Fyfanon® [malathion] and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A similar study found no effect of aerial spraying of pyrethrin synergized with piperonyl butoxide on mortality of sentinel urban bee colonies in California [ 6 ]. Similarly, a semi-field study assessing the impact of truck-based ULV mosquito adulticide applications on honey bees found minimal bee mortality compared to mosquito mortality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study found no effect of aerial spraying of pyrethrin synergized with piperonyl butoxide on mortality of sentinel urban bee colonies in California [ 6 ]. Similarly, a semi-field study assessing the impact of truck-based ULV mosquito adulticide applications on honey bees found minimal bee mortality compared to mosquito mortality [ 40 ].…”
Section: Discussionmentioning
confidence: 99%